Sustainability Reporting and Tax Aggressiveness: Evidence from a Public Company in Indonesia - Supriyati, Supriyati; Anggraini, Dwi Dita (Indonesian Journal of Sustainability Accounting and Management, 2021)
This study aims to describe tax avoidance or tax aggressiveness committed by a public company in Indonesia. To maintain company sustainability, taxation strategy must always be supported by a non-financial system. In Indonesia, sustainability report disclosure is voluntary, but the Indonesian government handles the issue by requiring the inclusion of social and environmental activities in the report as taxable operational costs. The research sample of this study comprises public companies listed on the Indonesia Stock Exchange, which have submitted sustainability reports separately. A total of 68 companies were involved, from which 132 datasets were obtained for further analysis via regression test. This research introduces a new way to measure tax aggressiveness (fiscal effective tax rate) to supplement the results generated by the existing measure (GAAP effective tax rate). The development of research shows that sustainability reporting has a significant effect on tax aggressiveness committed by public companies in Indonesia.